Advanced Paternal Age and Future Generations - Chan, Peter T. K.; Robaire, Bernard (Frontiers in Endocrinology, 2022)
Paternal age at conception has been increasing. In this review, we first present the results from the major mammalian animal models used to establish that increasing paternal age does affect progeny outcome. We then present the clinical observations relating advanced paternal age to fertility and effects on offspring with respect to perinatal health, cancer risk, genetic diseases, and neurodevelopmental effects. An overview of the potential mechanism operating in altering germ cells in advanced age is presented. This is followed by an analysis of the current state of management of reproductive risks associated with advanced paternal age. The numerous challenges associated with developing effective, practical strategies to mitigate the impact of advanced paternal age are outlined along with an approach on how to move forward with this important clinical quandary.